Influence of Human Disturbance on the Abundance of Himalayan Pheasant in the Temperate Forest of Western Himalaya, India - Jolli, V.; Pandit, M.K. (Вестник зоологии, 2011)
We conducted field studies in the Jiwa valley (Indian Himalayas) to examine the influence of human disturbance on Himalayan pheasants. We used the “call count” and “line transect” methods to estimate the abundance of pheasants in Jiwa valley. A human disturbance gradient defined by human population, agriculture activity, forest wood collection, grazing, vehicle, use of heavy machines, human settlements, dumping ground, and blasting was prepared.